PENGARUH SIKLUS HIDUP PERUSAHAAN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KEBIJAKAN DIVIDEN - Yasmina Dian Sativa; Eddy Suranta (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This study aims to provide empirical evidence of the influence of the corporate life cycle and institutional ownership on dividend policy. Dividend policy is measured by DivRate, DivTA, and DivPAT. The corporate life cycle is divided into 3 stages, namely growth, mature, and stagnant, which are measured using a multivariate cross-sectional approach by calculating the median values of median age, median sales growth, and median dividend policy. Institutional ownership is measured based on the percentage of institutional share ownership relative to total outstanding shares. The study sample of manufacturing companies listed on the IDX in 2015-2024. The sample selection method is the purposive sampling method which totals 342 observations. The results show that the corporate life cycle has an effect on dividend policy using the proxies DivRate, DivTA and DivPAT. Companies in the mature stage were not found to pay higher dividends than companies in the growth stage. Companies in the stagnant stage were found to pay higher dividends than companies in the growth stage. Companies in the stagnant stage paid higher dividends than companies in the mature stage. The results of further research prove that institutional ownership has a positive influence on dividend policy using the proxies DivRate, DivTA and DivPAT.